Impact of Vaccine Awareness Campaigns on Pharmacovigilance Reporting and Public Safety Monitoring - Suraj Sen; Anit Jha; Priyanshu Upadhyay; Rohit; Aman Kumar; Arvind Bhardwaj (International Journal of Vaccines, 2026)
Vaccination programs have significantly contributed to the reduction of infectious diseases worldwide; however, their success is closely tied to public confidence and robust safety monitoring systems. Pharmacovigilance plays a critical role in identifying, assessing, and preventing adverse events following immunization (AEFI). In recent years, vaccine awareness campaigns have emerged as a pivotal strategy to improve public knowledge, reduce vaccine hesitancy, and enhance reporting of adverse drug reactions (ADRs). This review explores the impact of vaccine awareness campaigns on pharmacovigilance reporting systems and overall public safety monitoring. It evaluates how educational interventions, media campaigns, and healthcare professional engagement influence reporting rates, data quality, and early detection of safety signals. Additionally, the article discusses global pharmacovigilance frameworks, reporting barriers, digital innovations, and the integration of awareness initiatives into surveillance systems. The findings suggest that awareness campaigns significantly improve spontaneous reporting rates, patient engagement, and transparency in vaccine safety monitoring. However, challenges, such as misinformation, underreporting, and variability in campaign effectiveness, persist. Strengthening communication strategies, integrating digital reporting tools, and fostering community trust are essential for optimizing pharmacovigilance outcomes.
Keywords: AEFI; Vaccine awareness; adverse drug reaction (ADR); drug surveillance; health communication; immunization programs; pharmacovigilance; public safety monitoring; reporting systems; vaccine hesitancy